2017
DOI: 10.1017/s0007114517002409
|View full text |Cite
|
Sign up to set email alerts
|

Mycoprotein represents a bioavailable and insulinotropic non-animal-derived dietary protein source: a dose–response study

Abstract: The anabolic potential of a dietary protein is determined by its ability to elicit postprandial rises in circulating essential amino acids and insulin. Minimal data exist regarding the bioavailability and insulinotropic effects of non-animal-derived protein sources. Mycoprotein is a sustainable and rich source of non-animal-derived dietary protein. We investigated the impact of mycoprotein ingestion, in a dose-response manner, on acute postprandial hyperaminoacidaemia and hyperinsulinaemia. In all, twelve heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 52 publications
3
76
1
Order By: Relevance
“…Glycaemic control was defined as blood glucose and insulin AUC or incremental AUC. In addition, for one study (29) , mean glucose levels (mmol/l) were reported at fasting (0 h), early (0-2 h) and late (2-4 h) postprandial stages. Energy intake was defined as acute energy intake (≤5 h post-ingestion) which included ad libitum meal and as short-term energy intake (>5 h post-ingestion) which included food diaries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Glycaemic control was defined as blood glucose and insulin AUC or incremental AUC. In addition, for one study (29) , mean glucose levels (mmol/l) were reported at fasting (0 h), early (0-2 h) and late (2-4 h) postprandial stages. Energy intake was defined as acute energy intake (≤5 h post-ingestion) which included ad libitum meal and as short-term energy intake (>5 h post-ingestion) which included food diaries.…”
Section: Discussionmentioning
confidence: 99%
“…In total, three randomised controlled and crossover trials assessed glycaemic control. Two studies (28,29) were conducted in healthy (no chronic disease such as type 2 diabetes), overweight (BMI 25-29•9 kg/m 2 ) and obese (BMI ≥ 30 kg/m 2 ) adults and one study (27) with healthy lean (BMI 18•5-24•9 kg/m 2 ) adults. Two studies were conducted using mycoprotein as liquid (27,29) , whereas one used mycoprotein as solid (28) .…”
Section: Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations